A Conceptual Ontology Framework for Culturally-Adaptive Mobile Learning Interfaces: Integrating the Indonesian Wellbeing Scale - Bhanu Sri Nugraha; Muhammad Suyanto; Kusrini; Ema Utami (Elinvo (Electronics, Informatics, and Vocational Education), 2025)
This research addresses the lack of cultural sensitivity in existing Adaptive User Interface (AUI) frameworks, which predominantly rely on Western-centric paradigms and often overlook the collective and spiritual dimensions of student well-being. To bridge this gap, this study proposes a conceptual ontology framework that operationalizes the Indonesian Wellbeing Scale (IWS) into computational adaptation logic for mobile learning applications. Adopting a Design Science Research approach utilizing the NeOn methodology, we formally modeled multidimensional context factors—specifically spiritual observances, social relations, and self-acceptance—into a machine-readable semantic taxonomy. The proposed ontology was rigorously validated using a two-tiered verification strategy: logical consistency checking via the HermiT reasoner and functional validation through Competency Questions (CQs) mapped to SPARQL queries. The results demonstrate that the framework successfully infers complex user needs and triggers appropriate interface adaptations, such as prioritizing community interactions during social isolation or scheduling spiritual alerts, without logical conflicts. This study contributes a validated computational model for Culturally-Adaptive User Interfaces, providing a robust semantic foundation for future physical implementation and empirical user evaluation.